A Filterable Agent Caused the Hemorrhagic Syndrome on Giant Gourami (Osphronemus goramy Lac.) at Yogyakarta - Nikmah, Nur Lailatul Fitrotun; Murwantoko (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Yogyakarta reported a new disease outbreak that infected giant gourami (Osphronemus goramy Lac.) broodstock in several locations. Typical clinical symptoms of the outbreak include bleeding and visceral adhesions. The River’s postulate suggests that the cause of the outbreak is a filterable agent. The filterable agent has the potential to be a new species or strain of the virus. Abstract Giant gourami (Osphronemus goramy Lac.) is one of the important freshwater fish commodities in Indonesia. Disease infection is one of the constraints in the production of this fish. There have been reports of disease outbreaks that caused mortality in giant gourami in several locations in Yogyakarta, including Gamping and Moyudan Districts, Sleman Regency; and Wates District, Kulon Progo Regency. This study describes the disease based on observations of external and internal signs, along with the histopathology of several tissues. Postulate river is used to prove the causative disease of the filterable agents. Polymerase Chain Reaction (PCR) and Reverse Transcriptase PCR (RT-PCR) are applied to confirm the presence of the virus. Sick fishes show the hemorrhage over the entire body surface, rotted fins, exophthalmia, petechiae, pale liver, visceral adhesions, and enlarged kidneys. Histopathological analysis shows lipidosis in the liver; bleeding in the liver, kidneys, spleen, and brain; and multiple necrosis in the kidneys, spleen, and brain. Based on these signs, we designated the disease to be Hemorrhagic Syndrome. The River postulate test confirmed that virus was the causative agent of the disease, as infecting healthy fish with a bacteria-free filtrate homogenate from diseased fish organs resulted in the same clinical signs observed in a natural outbreak. PCR tests for Megalocytivirus and EHNV, along with RT-PCR tests for VHSV, SVCV, TiLV, IHNV, and IPNV, did not show any DNA bands, indicating that these viruses were not present. A filterable agent, potentially representing a new virus species or strain, causes hemorrhagic syndrome in giant gourami.